Communicating with intelligence writing and briefing in national security - Major, James S. (Security and professional intelligence education series, 2014)
Communicating with Intelligence was the first book to teach the skills needed to make sure that papers, reports, and other products be correctly written by intelligence students and professionals. It also responded to the increased number of degrees in intelligence and national security offered in academic institutions.